Rice husk ash and fly ash geopolymer hollow block based on NaOH activated - Rattapon Somna; Teerapon Saowapun; Kiatsuda Somna; Prinya Chindaprasirt (Case Studies in Construction Materials, 2022)
This research aimed to utilize rice husk ash (RHA) to produce rice husk ash and fly ash (FA) geopolymer hollow block based on NaOH activated. RHA was ground for 15, 30, 60, and 90 min. The RHA to FA ratios of 10:90, 20:80, 30:70, 40:60, and 50:50 by weight and 14 molar sodium hydroxide were used. The compressive strengths of geopolymer paste were tested at 7, 28, and 60 days. The compressive strengths and percentages of water absorption of the geopolymer blocks were tested at 7 and 28 days. The microstructure of block was also characterized using SEM and mapping techniques. The results showed that the increase in RHA content increased the compressive strength of the geopolymer. The RHA contained amorphous silica and increase the SiO2/Al2O3 ratio and strength. The compressive strength of geopolymer increased with the increase in RHA fineness. The mix with 50% RHA content, i.e. 50FA50RH-15 M mix with 28-days compressive strength of 8.5 MPa was chosen to produce rice husk ash and fly ash geopolymer hollow block. The microstructure of rice husk ash and fly ash geopolymer hollow block showed the presence of the geopolymerization reaction products with small amount of unreacted RHA and FA particles. The carbon footprint of rice husk ash and fly ash geopolymer hollow block was around two-third of that of the Portland cement system. The result confirms that the rice husk ash and fly ash geopolymer hollow block could be used with compressive strength and water absorption complied with standard.